Synthesis and preliminary evaluation of N-oxide derivatives for the prevention of atherothrombotic events - Rosseto, Leandro Augusto [UNESP]; Pires, Maria Elisa Lopes; Melchior, Aylime Castanho Bolognesi [UNESP]; Bosquesi, Priscila Longhin [UNESP]; Pavan, Aline Renata [UNESP]; Marcondes, Sisi; Chin, Chung Man [UNESP]; Santos, Jean Leandro dos [UNESP] (Molecules, 2015)
Thrombosis is the main outcome of many cardiovascular diseases. Current treatments to prevent thrombotic events involve the long-term use of antiplatelet drugs. However, this therapy has several limitations, thereby justifying the development of new drugs. A series of N-oxide derivatives (furoxan and benzofuroxan) were synthesized and characterized as potential antiplatelet/antithrombotic compounds. All compounds (3a,b, 4a,b, 8a,b, 9a,b, 13a,b and 14a,b) inhibited platelet aggregation induced by adenosine-5-diphosphate, collagen, and arachidonic acid. All compounds protected mice from pulmonary thromboembolism induced by a mixture of collagen and epinephrine; however, benzofuroxan derivatives (13a,b and 14a,b) were the most active compounds, reducing thromboembolic events by up to 80%. N-oxide derivative 14a did not induce genotoxicity in vivo. In conclusion, 14a has emerged as a new antiplatelet/antithrombotic prototype useful for the prevention of atherothrombotic events.
Keywords: N-oxide; Antiplatelet activity; Atherothrombosis; Benzofuroxan; Bleeding time; Furoxan; Genotoxicity